Novel EGFRvIII-CAR transgenic mice for rigorous preclinical studies in syngeneic mice. (4th August 2021) - Chuntova, Pavlina; Hou, Yafei; Naka, Ryosuke; Yamamichi, Akane; Chen, Tiffany; Goretsky, Yitzhar; Hatae, Ryusuke; Nejo, Takahide; Kohanbash, Gary; Mende, Abigail L; Montoya, Megan; Downey, Kira M; et al.
Abstract: Background: Rigorous preclinical studies of chimeric antigen receptor (CAR) immunotherapy will require large quantities of consistent and high-quality CAR-transduced T (CART) cells that can be used in syngeneic mouse glioblastoma (GBM) models. To this end, we developed a novel transgenic (Tg) mouse strain with a fully murinized CAR targeting epidermal growth factor receptor variant III (EGFRvIII). Methods: We first established the murinized version of EGFRvIII-CAR and validated its function using a retroviral vector (RV) in C57BL/6J mice bearing syngeneic SB28 GBM expressing EGFRvIII. Next, we created C57BL/6J-background Tg mice carrying the anti-EGFRvIII-CAR downstream of a Lox -Stop- Lox cassette in the Rosa26 locus. We bred these mice with CD4-Cre Tg mice to allow CAR expression on T cells and evaluated the function of the CART cells both in vitro and in vivo. To inhibit immunosuppressive myeloid cells within SB28 GBM, we also evaluated a combination approach of CART and an anti-EP4 compound (ONO-AE3-208). Results: Both RV- and Tg-CART cells demonstrated specific cytotoxic activities against SB28-EGFRvIII cells. A single intravenous infusion of EGFRvIII-CART cells prolonged the survival of glioma-bearing mice when preceded by a lymphodepletion regimen with recurrent tumors displaying profound EGFRvIII loss. The addition of ONO-AE3-208 resulted in long-term survival in a fraction of CART-treated mice and those survivors demonstrated delayed growth of subcutaneously re-challenged both EGFRvIII + and parental EGFRvIII − SB28. Conclusion: Our new syngeneic CAR Tg mouse model can serve as a useful tool to address clinically relevant questions and develop future immunotherapeutic strategies.